Heterologous expression of MirMAN enhances root development and salt tolerance in Arabidopsis - Xu, Juanjuan; Yang, Caiyu; Ji, Shangyao; Ma, Hui; Lin, Jingwei; Li, Hui; Chen, Shuisen; Xu, Hai; Zhong, Ming (Frontiers in Plant Science, 2023)
Introduction β-Mannanase is a plant cell wall remodeling enzyme involved in the breakdown of hemicellulose and plays an important role in growth by hydrolyzing the mannan-like polysaccharide, but its function in adaptation to salt stress has been less studied. Methods Based on cloned the mannanase (MAN) gene from Mirabilis jalapa L., the study was carried out by heterologously expressing the gene in Arabidopsis thaliana, and then observing the plant phenotypes and measuring relevant physiological and biochemical indicators under 150 mM salt treatment. Results and discussion The results indicate that MirMAN is a protein with a glycohydrolase-specific structural domain located in the cell wall. We first found that MirMAN reduced the susceptibility of transgenic Arabidopsis thaliana to high salt stress and increased the survival rate of plants by 38%. This was corroborated by the following significant changes, including the reduction in reactive oxygen species (ROS) levels, increase in antioxidant enzyme activity, accumulation of soluble sugars and increase of the expression level of RD29 in transgenic plants. We also found thatthe heterologous expression of MirMAN promoted root growth mainly by elongating the primary roots and increasing the density of lateral roots. Meanwhile, the expression of ARF7, ARF19, LBD16 and LBD29 was up-regulated in the transgenic plants, and the concentration of IAA in the roots was increased. Those results indicate that MirMAN is involved in the initiation of lateral root primordia in transgenic plants through the IAA-ARF signalling pathway. In conclusion, MirMAN improves plant salt tolerance not only by regulating ROS homeostasis, but also by promoting the development of lateral roots. Reflecting the potential of the MirMAN to promote root plastic development in adaptation to salt stress adversity.